PENGARUH ELEKTROLISER TERHADAP KEPEKAAN BAHAN BAKAR PADA MESIN DIESEL 1 SILINDER 20 HP - Sutomo, Sutomo; Murni, Murni; Senen, Senen; Rahmat, Rahmat (Vocational School Diponegoro University, 2011)
Sutomo, Murni, Senen, Rahmat, Electrolyzer is development of a electrolysis technology to produce HHO gas, or Brownâ€™s gas. Diesel engine use solar (diesel oil) as combustionâ€™s material to produce thermal energy and oxidation and will be changed to mechanic energy. The base product of thermal energy by oxidation diesel oil, is would like to use electrolyzer to produce HHO and insert to the fuel combustion. Because HHO is a reactive gas, so in our research we hopeful will increase the thermal energy in combustion process and decrease the diesel oil consumption. The result of this research is the BSFC (Brake Shat Fuel Consumption) will decrease 2.5% up to 3.2%. Â Key word: electrolyzer, diesel engine, BSFC